2011
DOI: 10.1111/j.1365-2524.2011.01006.x
|View full text |Cite
|
Sign up to set email alerts
|

Family members’ experiences of personal assistance given to a relative with disabilities

Abstract: Personal assistance is a type of home care common to many countries even though entitlement and legislative framework may vary from country to country. At present, there exists no knowledge about the family members' experiences of such assistance; therefore, the aim of this study was to investigate family members' experiences of personal assistance given to a relative of working age with a functional disability. Twenty-five family members who had a relative with a severe neurological disease in Sweden were int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 24 publications
2
27
0
2
Order By: Relevance
“…In line with previous research, we found that nursing assistants struggled with lack of community in the home‐based setting (Ahlström & Wadensten , , Christensen ). Limited knowledge among primary healthcare professionals may be a key reason why families are wary of MND care provision (Brown et al .…”
Section: Discussionsupporting
confidence: 91%
“…In line with previous research, we found that nursing assistants struggled with lack of community in the home‐based setting (Ahlström & Wadensten , , Christensen ). Limited knowledge among primary healthcare professionals may be a key reason why families are wary of MND care provision (Brown et al .…”
Section: Discussionsupporting
confidence: 91%
“…Wang et al describe technology as complex and frightening for both families and healthcare professionals. Ahlström et al point out the challenge of having staff in the home day and night, with the accompanying loss of privacy, a HMV user can have up to twenty PCAs working in their home .…”
Section: Introductionmentioning
confidence: 99%
“…Under those circumstances, it was difficult to have a sense of purpose or achievement. Ahlström and Wadensten [33] report that having a small care staff implies security and contributes to increased client satisfaction.…”
Section: Discussionmentioning
confidence: 99%